The Rights of Patients as Consumers of Health Care Services In The Transaction of The Therapeutic - Deetje Christy Anggraini; Etty Marjati (Faculty of Law, Merdeka University Surabaya, 2020)
The therapeutic is a legal relationship between the doctor with patient medical services professionally based whose competence in accordance with sophistication and skill in particular in medical field ( Komalawati,1999:1 ). As a legal relationship and has rights and duties of the parties which were elements of that cannot be separated from the therapeutic. In contrast to engagements in general have, similarity in it so frequently in the therapeutic imbalance each other parties as the seat of the knowledge and understanding of, engagements hence the legal duty to provide balance through recognition and protection laws against rights patients in the underlying transactions law. was therapeutic. The rights of patients that rises of two the basic rights of the right to health care and the right of self determination In the implementation have to reflect the values of human rights back, in addition to fulfill their rights these patients also could become one of the indicators to obligation that should be adopted by a doctor.